Patient-Reported Outcome Following Operative and Conservative Treatment of Calcaneal Fractures: A Retrospective Analysis of 79 Patients at Short- to Midterm Follow-Up - Pflüger, Patrick; Zyskowski, Michael; Greve, Frederik; Kirchhoff, Chlodwig; Biberthaler, Peter; Crönlein, Moritz (Frontiers in Surgery, 2021)
Background: Fractures of the calcaneus are severe injuries of the hindfoot, mostly resulting from high energy axial loads still presenting enormous challenges to modern trauma surgery. Possible variables influencing the outcome are type of fracture, age and quality of fracture reduction. These might also be factors affecting the self-reported patient outcome, but large studies are still lacking. Therefore, the aim of this study was to analyze patient reported outcome of calcaneal fractures following operative and conservative treatment. Methods: All patients suffering from calcaneal fractures between 2002 and 2015 were enrolled in this retrospective analysis. The calcaneal fractures were classified according to Sanders and the AO classification system. For further analysis, two groups were formed: group I involved complex intra-articular fractures defined by the involvement of the posterior calcaneal facet. Group II consisted of extra-articular and process calcaneal fractures. Data was collected via the patient registry, radiographs and a standardized questionnaire (Foot and Ankle Outcome Score = FOAS). For outcome analysis, the nonparametric Mann-Whitney U test was performed and Spearman’s rank correlation coefficient calculated. Results: In total, the functional outcome of 79 patients with calcaneal fractures was analyzed. In group 1 (n=43) the mean FAOS score was 65.5+/-18.9. Surgically treated patients with a Sanders type II calcaneal fracture had a mean FAOS score of 72.9+/-17.2, type III fractures of 65.6+/-20.8 and type IV of 61.1+/-19 (p=0.15). The reoperation rate was 22%, most frequently caused by wound complications (10%). The mean follow-up time was 64.544 months. The mean FAOS score of group 2 (n=36) was 75.2+/-18.4 and 83% of the patients (=30) were managed conservatively. Only one out of six operatively managed patients had a reoperation due to regular implant removal. The mean follow-up time was 31+/-25.9 months. Conclusion: Intra-articular calcaneal fractures are severe injuries of the hindfoot leading to a fair to poor functional outcome in the majority of the patients. Complications regarding wound healing are the most common causes for revisional surgery. Extra-articular calcaneal fractures are a heterogenous entity commonly managed nonoperatively. Overall, they show a better functional outcome in comparison to intra-articular calcaneal fractures.